21st century medical education: critical decision-making guidance through smartphone/tablet applications—the Lothian pilot. (16th January 2017) - Prescott, Oliver; Millar, Eoghan; Nimmo, Graham; Wales, Ann; Edgar, Simon
Abstract : Introduction: In starting a new clinical placement, doctors in training must become aware of and apply standard operating procedures, as well as learn guidelines, simultaneously adjusting to new patient presentations, environments and personnel. This transition is thought to correlate with increased risk to patient safety, notably during the annual UK changeover. Mobile technologies are increasingly commonplace throughout the National Health Service. Clinicians at all levels are employing medical technology and applications (apps) with minimal local guidance. We set out to test the feasibility and utility of offering medical apps to out-of-hours (OOH) practitioners as an aid to clinical decision-making at point of patient contact. The theorised benefits were threefold: clinical education—real time support for clinical decision-making as one component of deliberate practice to build expert performance; decreased administrative burden–updating and accessing current guidelines; and service development—readily accessible feedback from users. Method: We provided 32 devices in our emergency departments and OOH environments. The devices were preloaded with apps approved by our medical education department and clinical service leads to be used in support of care delivery. Results: We surveyed 123 clinical staff prior to the pilot discovering that 65% had used mobile apps to aid their decision-making. During our project, we saw the number of clinical users expand with our data series, suggesting the apps most useful to care delivery for this group of service providers. Future developments: There was huge enthusiasm for the project and we hope to maintain a clinician-led environment.